Secure Data Sharing For Collaborative Medical Research (International Journal of Environmental Sciences, 2025)
Sharing medical data can enhance teamwork, accessibility, and patient care, which will ultimately result in better results and more effective healthcare delivery. Due to the delicate nature of medical data, strong privacy and secrecy are required. Despite the exploration of access control approaches, data privacy issues persist and call for additional solutions. Using private set intersection and key aggregation encryption, the proposed study presents a privacy-preserving data-sharing approach that strikes a compromise between security and secrecy, safeguarding sensitive information while it is being shared. We conduct both formal and informal security studies, demonstrating the resilience of Burrow-Abadi-Needham logic to potential adversarial attacks. The study compares the suggested scheme against current ones in terms of security, computational complexity, and time complexity using a cryptography library to assess execution time. The suggested plan exhibits encouraging outcomes, providing high security and efficiency while safeguarding data privacy and permitting secure, adaptable medical data exchange, making it a useful tool for the industry.